Jerusalem embattled : a diary of the city under siege, march 25th, 1948 to july18th, 1948 - Levin, Harry (London : Gollancz, 1950)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Arabisch-Israëlisch conflict; egodocumenten; Israël